Factors that Cause Differentiation in Academic Performance Between Public and Private Primary Schools in Igembe North Subcounty, Meru County, Kenya - Maore, Janet Mwoburi; Kathuri, N. J.; Kigo, Josephat K. (International Journal For Research In Educational Studies, 2019)
Learners’ academic performance has lured the interest of scholars, parents, policy makers, planners and curriculum implementers. The main objective of schools is to ensure that learners achieve academic excellence. Private primary schools in Igembe North have been performing far much better than public primary schools. It is not clear as to what factors that cause this difference.This study aimed at investigating the factors that caused differentiation in academic performance between public and private primary schools in Igembe North sub county of Meru County, Kenya. The study employed expost-facto research design. The target population included 83 head teachers, 83 senior teachers and 3550 pupils, making a total of 3716 subjects. A sample of 250 respondents - 25 head teachers, 25 senior teachers, 200 pupils was randomly and proportionately drawn from the target population. The researcher used questionnaires to collect data from the respondents.Pilot study was done in two schools outside Igembe North Sub County, to assess the quality of the instruments. Once the quality of the instruments was ascertained, the researcher visited the selected primary schoolsand planned with the school head teachers on data collection in their respective schools. After all the respective data was collected it was sorted out and then analysed using Statistical Package for Social Sciences (SPSS) version 18. Descriptive, t – test, and Chi square statistics, as well as, Pearson correlation analyses were used to analyze factors that cause differentiation in Academic performance between public and private primary schools in Igembe North Sub County. It was established that eight of the ten head teachers’ characteristics items significantly varied between private and public primary schools. Besides, six of the ten teachers’ characteristics items, nine of the ten pupils’ characteristics items and all the eleven parents’ characteristics items differed significantly between private and public primary schools. It was consequently recommended that the TSC, ministry of education and head teachers should stimulate the necessary motivation among public primary schools teachers, provide the necessary and adequate teaching and learning resources, as well as, encourage participation of parent in school teaching/ learning process, respectively.